2020
DOI: 10.1016/j.radonc.2020.03.029
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy workflow and protection procedures during the Coronavirus Disease 2019 (COVID-19) outbreak: Experience of the Hubei Cancer Hospital in Wuhan, China

Abstract: Acknowledgements: None. months of uninterrupted radiation oncology clinical operation through the worst of the Wuhan outbreak, no known COVID-19 infection occurred at our radiotherapy center to our patients or employees. This report may provide valuable information for other radiation oncology departments during this unprecedented public health crisis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
140
0
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(152 citation statements)
references
References 16 publications
(19 reference statements)
0
140
0
12
Order By: Relevance
“…This, combined with the considerable rate of transmission from asymptomatic subjects [33] and the incubation time [34], could justify the high incidence of infection in the initial two weeks. The strict application of a dedicated work ow and the constant adoption of adequate PPE [35][36] allowed us not only to contain and almost neutralize the diffusion of the infection, but also to carry on radiation therapy in patients positive for SARS-Cov-2 with mild or asymptomatic disease. The infection rate among patients undergoing treatment at our department outstandingly precipitated to 0.43% considering the period from March 25 to April 24 and no new contagion among our staff was observed in this time span.…”
Section: Covid-19 Impact On the Staffmentioning
confidence: 99%
“…This, combined with the considerable rate of transmission from asymptomatic subjects [33] and the incubation time [34], could justify the high incidence of infection in the initial two weeks. The strict application of a dedicated work ow and the constant adoption of adequate PPE [35][36] allowed us not only to contain and almost neutralize the diffusion of the infection, but also to carry on radiation therapy in patients positive for SARS-Cov-2 with mild or asymptomatic disease. The infection rate among patients undergoing treatment at our department outstandingly precipitated to 0.43% considering the period from March 25 to April 24 and no new contagion among our staff was observed in this time span.…”
Section: Covid-19 Impact On the Staffmentioning
confidence: 99%
“…29 At any given time, 33% to 50% of staff should be working at the clinic. 30 Staff must get training in donning and doffing of personal protective equipment and should be provided with appropriate PPE. 31,32 The staff should be encouraged to do frequent hand washing with soap and water for at least 20 seconds.…”
Section: Consensus Guidelines For the Staff Rotation And Training Imentioning
confidence: 99%
“…These strategies have been described in depth in reports from China, Italy and the United States of America. [52][53][54][55] Meanwhile, a patient who tests positive for COVID-19 and is asymptomatic, may still be considered physiologically unfit to tolerate any further lung cancer therapies as many patients develop worsening symptoms in the second week of infection. 56 Early studies have shown that COVID-19 can lead to acute respiratory distress syndrome with pathological changes such as destruction of the alveoli and cellular fibromyxoid exudates.…”
Section: Covid-19 Infected Patientsmentioning
confidence: 99%